Structure-activity correlations for Brønsted acid, Lewis acid, and photocatalyzed reactions of exfoliated crystalline niobium oxides - Koito, Y; Rees, G; Hanna, J; Li, M; Peng, Y; Puchtler, T; Taylor, R; Wang, T; Kobayashi, H; Teixeira, I; Khan, M; Kreissl, H; et al. (Wiley, 2016)
Exfoliated crystalline niobium oxides that contain exposed but interconnected NbO 6 octahedra with different degrees of structural distortion and defects are known to catalyze Brønsted acid (BA), Lewis acid (LA), and photocatalytic (PC) reactions efficiently but their structure–activity relationships are far from clear. Here, three exfoliated niobium oxides, namely, HSr 2 Nb 3 O 10 , HCa 2 Nb 3 O 10 , and HNb 3 O 8 , are synthesized, characterized extensively, and tested for selected BA, LA, and PC reactions. The structural origin for BA is associated mainly with acidic hydroxyl groups of edge-shared NbO 6 octahedra as proton donors; that of LA is associated with the vacant band position of Nb 5+ to receive electron pairs from substrate; and that of PC is associated with the terminal Nb=O of NbO 6 octahedra for photon capture and charge transfer to long-lived surface adsorbed substrate complex through associated oxygen vacancies in close proximity. It is believed that an understanding of the structure–activity relationships could lead to the tailored design of NbO x catalysts for industrially important reactions.